Extracorporeal cardiopulmonary resuscitation in adults and children: A review of literature, published guidelines and pediatric single-center program building experience - Olson, Taylor; Anders, Marc; Burgman, Cole; Stephens, Adam; Bastero, Patricia (Frontiers in Medicine, 2022)
Extracorporeal cardiopulmonary resuscitation (ECPR) is an adjunct supportive therapy to conventional cardiopulmonary resuscitation (CCPR) employing veno-arterial extracorporeal membrane oxygenation (VA-ECMO) in the setting of refractory cardiac arrest. Its use has seen a significant increase in the past decade, providing hope for good functional recovery to patients with cardiac arrest refractory to conventional resuscitation maneuvers. This review paper aims to summarize key findings from the ECPR literature available to date as well as the recommendations for ECPR set forth by leading national and international resuscitation societies. Additionally, we describe the successful pediatric ECPR program at Texas Children's Hospital, highlighting the logistical, technical and educational features of the program.